Biomass‐assisted Zeolite Syntheses as a Tool for Designing New Acid Catalysts. Issue 12 (22nd May 2017) - Louis, Benoît; Gomes, Elisa S.; Losch, Pit; Lutzweiler, Gaëtan; Coelho, Tiago; Faro, Arnaldo; Pinto, Joana F.; Cardoso, Cristiane S.; Silva, Alessandra V.; Pereira, Marcelo M.
Abstract: The aim of this Concept article is to highlight different aspects of using biomass residues or extracted molecules in the synthesis of zeolites (mainly), aluminas and layered doubled hydroxides (LDHs). The strategies presented should serve as a basis for rationally preparing those aforementioned materials for catalytic purposes. Indeed, the presence of sugars, lignin, lignocellulosic biomass usually induces morphological/textural changes as well as (in some cases) modified chemical composition and surface properties. Abstract : Biomass‐based zeolites : This Concept describes different aspects of using biomass residues or extracted molecules in the synthesis of zeolites (mainly), aluminas, and layered doubled hydroxides. Additionally, how the presence of sugars, lignin, lignocellulosic biomass usually induces morphological/textural changes, as well as modified chemical composition and surface properties.